Myocardial damage, coagulation activity and the response to thrombin inhibition in unstable coronary artery disease - Oldgren, Jonas; Siegbahn, Agneta; Grip, Lars; Linder, Rikard; Thygesen, Kristian; Wallentin, Lars (Thrombosis and Haemostasis, 2004)
Unstable coronary artery disease is in most cases associated with plaque rupture, activation of the coagulation system and subsequent intracoronary thrombus formation which may cause myocardial cell damage. The aim of the present analysis was to assess the relation between troponin T, markers of coagulation activity, i.e. prothrombin fragment 1+2, thrombin-antithrombin complex, soluble fibrin and D-dimer, and ischemic events, i.e. death, myocardial (re-)infarction or refractory angina. 320 patients with unstable coronary artery disease were randomized to 72 hours infusion with inogatran, a low molecular weight direct thrombin inhibitor, or unfractionated heparin. Patients with elevated troponin levels had higher levels of prothrombin fragment 1+2, soluble fibrin and D-dimer before, during, and at 24 hours after cessation of anticoagulant treatment. These troponin-positive patients tended to have worse short-term clinical outcome, without relation to markers of coagulation activity. Troponin-negative patients with unchanged or early increased thrombin generation during treatment had a cluster of ischemic events within 24 hours after cessation of the study drug. The 30-day ischemic event rate was 19 % in troponin-negative patients with unchanged or early increased prothrombin fragment 1+2, and 5.7 % in patients with decreased prothrombin fragment 1+2, p=0.006, and similarly 15 % in troponin-negative patients with unchanged or early increased thrombin-antithrombin complex and 4.5 % in patients with decreased thrombin-antithrombin complex, p=0.02. In conclusion, in unstable coronary artery disease a troponin elevation indicates higher risk and higher coagulation activity. However, among the troponin negative patients, with a lower risk and lower coagulation activity, a part of the patients seem to be non-responders to treatment with a thrombin inhibitor expressed as unchanged or raised coagulation activity and a raised risk of ischemic events early after cessation of treatment.
Keywords: Clinical trials; direct antithrombin agents; coagulation inhibitors; ischaemic heart disease